CEO Power and Nonconforming Reference Group Selection - Audia, Pino G.; Rousseau, Horacio E.; Brion, Sebastien (Organization Science, 2022)
Research shows that reference group selection underpins critical organizational processes, but less is known about publicly disclosed choices of reference groups, such as those for the evaluation of firm performance. Because audiences, such as investors and analysts, prefer reference groups created by independent entities they can trust, they disapprove of choices of custom peer groups created by reporting firms. Nevertheless, firms frequently choose reference groups that do not conform to audiences’ expectations. We seek to explain why firms deviate from these externally held standards even when incurring penalties by developing theory and formulating hypotheses about the influence of chief executive officer (CEO) power. Using data from 10-K filings, we find that firms led by high-power CEOs are more likely to use nonconforming, custom peer groups despite incurring penalties. However, the relationship between CEO power and the use of custom peer groups is weaker when CEOs face greater scrutiny from shareholders and analysts. We also find that low firm performance increases the use of custom peer groups among high-power CEOs. Contrary to our expectations, high CEO compensation attenuates the effect of CEO power on the choice of custom peer groups, arguably because high levels of CEO pay increase scrutiny. Although firms incur costs for using nonconforming reference groups, supplemental analyses reveal that CEOs benefit by receiving higher compensation, especially when performance is low. We conclude by discussing implications for research on publicly disclosed reference groups, the consequences of power, and information disclosure.